A biodegradable gelatin-based nanostructured sponge with space maintenance to enhance long-term osteogenesis in maxillary sinus augmentation. (January 2021) - Ying, Yiqian; Li, Beibei; Liu, Changying; Xiong, Zuochun; Bai, Wei; Li, Jun; Ma, Pan
The search for bone substitutes that are biodegradable, ensure space maintenance, and have osteogenic predictability, is ongoing in the field of sinus augmentation. We thus compared the bone regeneration potential of nanostructured sponges (NS-Sponge) with that of collagen-stabilized inorganic bovine bones (BO-Collagen), gelatin sponges (Gelatin), and blood clots (Cont) in sinus augmentation of rabbits. NS-Sponge was prepared by thermally induced phase separation with porogen leaching techniques. All the materials were non-hemolytic and cytocompatible. The porous and nanofibrous NS-Sponge showed better dimensional stability to support cell growth and osteogenic differentiation. In vivo, the sinus membrane collapsed in Cont and Gelatin, while BO-Collagen and NS-Sponge maintained the elevated height as assessed by come-beam computed tomography. Limited bone regeneration was observed in Cont and Gelatin. In the entire implanted area, histological analysis revealed a higher percentage of new bone area at 4 weeks of BO-Collagen treatment; however, a significantly greater increase in new bone area was observed after 12 weeks of NS-Sponge treatment. The 12-week remnant NS-Sponge material was significantly lower than the 4-week remnant material. Overall, NS-Sponge may be highly recommended for sinus augmentation, as it exhibits numerous advantages, including excellent operability, clear imaging characteristics, space maintenance, biodegradability, and superior osteogenic potential.